Sanksi Adat Terhadap Perkawinan Sumbang Nikah Perspektif Hukum Keluarga Islam (Studi di Desa Sibak Kecamatan Ipuh Kabupaten Mukomuko) - Saputra, Ari; Nurdin, Zurifah; Marhayati, Nelly (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstracts: The formulation of this research is: 1) What is the practice of 'Sumbang Nikah' marriage in Sibak Village, Ipuh District, Mukomuko Regency 2) How does Islamic law view customary sanctions against 'Sumbang Nikah' marriage in Sibak Village, Ipuh District, Mukomuko Regency. This type of research is qualitative research, data collection techniques using observation, interviews and documentation. This research concludes that 1) The practice of